2016
DOI: 10.1371/journal.pone.0158654
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Extracted Brazilian Propolis Exerts Protective Effects on Tumorigenesis in Wistar Hannover Rats

Abstract: The present study was conducted over a course of 104 weeks to estimate the carcinogenicity of ethanol-extracted Brazilian green propolis (EEP). Groups of 50 male and 50 female Wistar Hannover rats, 6-week-old at commencement were exposed to EEP at doses of 0, 0.5 or 2.5% in the diet. Survival rates of 0.5% and 2.5% EEP-treated male and female rats, respectively, were significantly higher than those of respective control groups. Overall histopathological evaluation of neoplasms in rat tissues after 2 years show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Recently, Kakehashi et al demonstrated that 2-year administration of 2.5% EEP in the diet exerted anticarcinogenic potential and significantly reduced the incidence of several naturally occurring tumors in male and female rats (38). These results taken together with the results of the present study suggest that propolis could be developed as a supportive product targeting patients with IBD, including patients with ulcerative colitis and Crohn's disease, who may continuously need anti-inflammatory drugs.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Recently, Kakehashi et al demonstrated that 2-year administration of 2.5% EEP in the diet exerted anticarcinogenic potential and significantly reduced the incidence of several naturally occurring tumors in male and female rats (38). These results taken together with the results of the present study suggest that propolis could be developed as a supportive product targeting patients with IBD, including patients with ulcerative colitis and Crohn's disease, who may continuously need anti-inflammatory drugs.…”
Section: Discussionsupporting
confidence: 75%
“…A previous study showed the median lethal dose (LD 50 ) of propolis and its flavonoids in an acute oral toxicity test to be 4-8 g/kg in rats, and no adverse effects were seen in rats administered 2.74 g/kg b.w./day for 60 days via their drinking water (37). Two-year feeding of 2.5% EEP, corresponding to 1-2 g/kg/day, revealed no carcinogenicity in any organs in male or female rats (38). Therefore, daily intake of 0.42-0.44 g/kg of EEP and WEP by rats appears to be well below toxic levels.…”
Section: Resultsmentioning
confidence: 94%
“…This shows the plants concentrate may not pose hepatic damage since the concentration of albumin and total protein were within range and may be viable in hoisting hypoalbuminemia that may happen in breast tumour patients. The total protein and albumin concentration of this study was similar to those of Kakehashi, et al [18], which demonstrated that total protein and albumin was 68-69g/l and 31-34g/l respectively, in tumorigenic wistar rats. Although it was higher than those animals treated with Punica granatum (albumin as 27.2-31.8g/l and total protein as 42.4-54.6g/l) [19].…”
Section: Discussionsupporting
confidence: 89%
“…This manner validates that the concentrate possesses no deleterious impact on total bilirubin and conjugated bilirubin concentration. The total bilirubin concentration of this present study was higher than Baccharis dracunculifolia (3.42µmol/l) [18] but lower than Punica granatum (18.29-22.25µmol/l) [19] treated mammary tumorigenic animals.…”
Section: Discussionmentioning
confidence: 71%
“…An automated hematology analyzer (Sysmex XE-2100, Mitsubishi Chemical Visuals, Osaka, Japan) and an automatic analyzer (Olympus AJ-5200, Tokyo, Japan) were employed for hematological and biochemical analyses of blood serum as previously described [36]. …”
Section: Methodsmentioning
confidence: 99%